Physical Planning and Management of Modern Health Care Facilities in the Rural Area of Ondo State, Nigeria (2014)
Studies on health care facilities, apart from being urban biased, have focused more on spatial inequality and patronage pattern to the neglect of physical planning and management. This study, therefore, evaluated the distribution pattern of the facilities, degree of conformity with planning standard and perception of their management in the rural areas of Ondo state, Nigeria. Ondo state was chosen due to its peculiar characteristics of having upland, midland and coastland areas. A cross-sectional survey research design was adopted. A combination of the central place and environmental planning and management theories, and three delay model guided the study. A multi-stage sampling technique was adopted to select one rural Local Government Area (LGA) in each senatorial district. A total of 328 rural settlements were identified in the selected LGAs, out of which eleven with modern healthcare facilities were purposively selected. Nine hundred and ninety-eight households were chosen for the study. A structured questionnaire on socio-demographic characteristics (age, sex), physical planning variables (distance travelled, mode of travel) and management variables (community involvement in decision making) was administered to respondents. Observational checklist was used to assess physical planning standards in relation to the facilities (land area, building density, open space, bed space, road, and topography). Key-Informant Interviews (KII) and Focus Group Discussions (FGDs) complemented information on facilities’ management. The KIIs were conducted with the chairmen, community development officers, directors of town planning and senior health officers in the LGAs. Four FGDs were constituted in each LGA. Secondary data on physical planning attributes (threshold population and range) were also sourced. Descriptive statistics and Nearest Neighbour Analysis were employed to determine the spatial pattern of the facilities. Qualitative data were content analysed. The respondents’ mean age was 39.1 ±12.3 years, 52.6% were males. About 90% of the respondents travelled more than the expected maximum five kilometers, and 68.0% walked to health care facilities. Management of healthcare facilities was perceived by the respondents to be inadequate in terms of supervision (57.1%), irregular meetings (54.6%) and poor community dialogue (75.5%). Challenges to healthcare facilities identified by the respondents included: finance (63.2%), non-availability of modern equipment (56.0%) and shortage of medical and paramedical staff (43.0%). Field observations revealed that none of the facilities satisfied the physical planning regulation’s requirements for land area, building density, open space, and bed space, while 64.0 % and 71.4% met the requirements for road and topographical standards respectively. Variations were also observed in the level of compliance with the physical planning regulation standards among the senatorial districts: Ondo north (23.0 %) > Ondo central (16.4%) > Ondo south (12.3%). All health care facilities surveyed did not have the required threshold population needed to guarantee adequate patronage. Modern health care facilities were clustered (Rn < 1). Top-down planning and management approach to health care facilities was observed. Modern health care facilities in the rural areas of Ondo state were poorly distributed. Enforcement of compliance to planning and management standards is recommended.